49. Iron Ore Deposits of the Iron Springs District, Southwestern Utah - J. Hoover Mackin (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
The iron ore bodies of the Iron Springs district are replacement deposits of magnetite and hematite in Jurassic limestone around the borders of three intrusions of quartz-monzonite porphyry. Production in the period 1923-1965 was about 72,000,000 tons, nearly all of which was direct-shipping ore from open pits. The intrusions are laccolithic in form; all three were emplaced at the same stratigraphic horizon, which had been a zone of decollement gliding during the Laramide orogeny. The intrusions and associated volcanic rocks are post-orogenic. There was no change in the thickness of the limestone during the metallization. Comparison of the composition of the limestone and stratigraphically equivalent replacement ore indicates that, with every million tons of iron, there were additions of 40,000 tons of silicon, 20,000 tons of magnesium, and 10,000 tons of aluminum. The ore-forming fluid was derived from the exposed porphyry. The iron was first incorporated in hydroxyl-bearing mafics, which crystallized in depth and were carried upward in the magma that formed the hypabyssal intrusions. The mafic phenocrysts decayed deuterically in the new environment, releasing iron into the interstitial fluid of a consolidating crystal mush in the interior of the intrusions. Primary tension joints, which opened in areas of late intrusive distention, served as roots through which the ore-forming fluid was drawn from the crystal mush.